PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS MENGGUNAKAN MODEL PEMBELAJARAN ARIAS DI KELAS IV SEKOLAH DASAR - anggraini, maulia; Hamimah, Hamimah; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract The purpose of this research is to improve the learning outcome from the student in social science knowledge which using ARIAS model at fourth grade student from elementary school of 06 Piai Tangah Padang City. The subject at this research is the student from elementary school of 06 Piai Tangah Padang City. The data from this research obtainable from the result of observation on the action from the student. The results of each cycle are: (a) The result of the research indicated that there was an improvement on the lesson plan from 82% to 92,8% . (b) the teacher aspects increased from 82,1% to 92,8%). The student aspects increased from 80,3% to 92,8%. (c) The learning score increased from 74,5% to 86,1%. Thus, the ARIAS model can improve student learning outcomes in social science knowledge fourth grade student from elementary school of 06 Piai Tangah Padang City. Key words: Learning score social science, ARIAS model